Establishing a Long-Term Model for Analysis and Improvement of Underfilled Blood Culture Volumes. Issue 2 (26th September 2018) - Zaleski, Michael; Erdman, Patrick; Adams, Joshua; Michael, Amanda; Rudy, Abigail; Boesch, Robert; Allison, Lauren; Mailander, Patricia; Hess, Wendell; Myers, Debra; Craft, David
Abstract: Objectives: Underfilling of blood culture bottles decreases the sensitivity of the culture. We attempt to increase average blood culture fill volumes (ABCFVs) through an educational program. Methods: Partnerships were established with four hospital units (surgical intensive care unit [SICU], medical intensive care unit [MICU], medical intermediate care unit [MIMCU], and hematology and oncology unit [HEME/ONC]). ABCFVs were continuously tracked and communicated to each unit monthly. Educational sessions were provided to each unit. Results: ABCFVs for the SICU, MICU, MIMCU, and HEME/ONC were 4.8, 5.0, 5.0, and 6.3 mL/bottle, respectively. After the final education session, the SICU, MICU, MIMCU, and HEME/ONC were able to maintain an ABCFV of 6.8, 8.1, 7.9, and 8.2 mL/bottle, respectively. Conclusions: Partnering with a specific unit and providing monthly volume reports with educational sessions has a direct positive correlation on increasing ABCFVs. Increasing ABCFVs has the potential to decrease false-negative blood cultures, time to detection of positive blood cultures, and time to appropriate and specific antimicrobial therapy, as well as improve patient outcomes in high-acuity patient care units.